The role of vascular calcification in inducing fatigue and fracture of coronary stents - Halwani, Dina O.; Anayiotos, Andreas (My University, 2011)
Traditional approaches for in-vitro pulsatile and fatigue testing of endovascular stents do not take into consideration the pathologies of the stented vessel and their associated biomechanical effects. One important pathology is calcification, which may be capable of inducing changes in the vessel wall leading to inhomogeneous distribution of stresses combined with wall motion during the cardiac cycle. These local property changes in the region adjacent to stents could directly influence in-vivo stent performance. Seven cases containing a total of 18 stents were obtained from autopsy. Radiographs were evaluated and vessels were sectioned for histology and stent topographical analysis. Stents were retrieved by chemical removal of surrounding tissue and surfaces were evaluated using 3D digital optical and scanning electron microscopy for biomechanical abrasion and fracture features. Pathologic complications such as restenosis and thrombus formation were assessed from histological sections. Direct evidence of fracture was found in 6 of the 7 cases (in 12 out of 18 stents; 9 drug eluting and 3 bare metal). The degree of stent alterations was variable, where separation of segments due to fracture occurred mostly in drug-eluting stents. All fracture surfaces were representative of a high cycle fatigue mechanism. These fractures occurred in complex lesions involving the presence of diffuse calcification alone, or in combination with vessel angulations and multiple overlapping stents. Morphologic analysis of tissue at or near some fracture sites showed evidence of thrombus formation and/or neointimal tissue growth.
Keywords: Calcification; In-stent restenosis; Overlapping stents; Fatigue; Stent fracture